ANALYSIS OF EFFECT OF FORMAL RULES FOR FINANCIAL POSITION JOINT BUSINESSES IN THE STAVROPOL REGION - Natalya Krivorotova (Вестник Северо-Кавказского федерального университета)
The article deals with the current state and prospects of development of joint business in the region. Presented specific structure offoreign investment, territorial and sectoral structure of joint ventures Stavroplskogo edge, as well as the structure of foreign direct investment by major investing countries. Particular attention is paid to the analysis of the impact offormal rules and consumer potential of the joint enterprise in the region